Assessment of the Levels of Customer Satisfactions Towards the Services Offered by Kabayan Pares Mami at A. Mariano, Bagbaguin, Valenzuela City Year (2022-2023): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The owners of Kabayan Pares Mami decided to start a small business located near a school,factory, and wet market. It is a great location to start a business. Kabayan Pares Mami facesmany different problems and complaints from their customers where they address the smallportion of the product and the limited seats available. These instances led to unsatisfiedcustomers. The researchers made a survey questionnaire for the customers to fill out wherethey can give suggestions for the improvement of the business.Based on the results, the significant difference in the level of customer satisfaction betweenemployed and unemployed customers of Kabayan Pares Mami revealed that there is nosignificant difference in the level of customer satisfaction between employed customers andunemployed customers in terms of Serving Time (t-stat value of 0.458831 and 0.67018 withp-value) respectively leads to accepting the nulled hypothesis while the level of customersatisfaction between employed customers and unemployed customers in terms ofCompleteness of Orders has significant difference (t-stat value of 5.962848 and 0.00397with p-value) which leads to rejecting the nulled hypothesis. Lastly, the level of customersatisfaction between employed customers and unemployed customers in terms of Hospitalityfound that there is no significant difference (t-stat value of -0.693334 and 0.52625 with p-value) that leads to accepting the nulled hypothesis.The findings show that the majority of the respondents are 18-29 years old, male and single.The level of customer satisfaction in Kabayan Pares Mami between two groups ofrespondents in terms of serving time, completeness of orders, and hospitality is “HighlySatisfied.” There is no significant difference between an assessment of two groups ofrespondents as to the cited variables. The biggest challenge encountered by the customersof Kabayan Pares Mami is the Limited seats available. The researchers propose guidelinesand recommendations to help Kabayan Pares Mami enhance the level of their customersatisfaction to retain and acquire more customers.
Keywords: Business Administration